2012
DOI: 10.1155/2012/638240
|View full text |Cite
|
Sign up to set email alerts
|

Elastic Properties of Natural Sea Surface Films Incorporated with Solid Dust Particles: Model Baltic Sea Studies

Abstract: Floating dust-originated solid particles at air-water interfaces will interact with one another and disturb the smoothness of such a composite surface affecting its dilational elasticity. To quantify the effect, surface pressure (Π) versus film area (A) isotherm, and stress-relaxation (Π-time) measurements were performed for monoparticulate layers of the model hydrophobic material (of μm-diameter and differentiated hydrophobicity corresponding to the water contact angles (CA) ranging from 60 to 140• ) deposite… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…In “real” systems, in technology, biology, and oceanography, surfaces are often non-uniform. For instance, a flat surface containing a surfactant monolayer which has undergone a two-dimensional phase separation falls under this definition, as well as air-water and oil-water interfaces with droplets, solid particles, or even thin layers of a microemulsion, foam, or a bicontinuous phase of complex surface thermo and viscoelastic properties (Maestro et al 2015 ; Maestro et al 2014 ; Mazurek and Pogorzelski 2012 ). Addition of surface-active component to seawater can lead to complex formation and affect the interfacial properties (Guzman et al 2014 ).…”
Section: Resultsmentioning
confidence: 99%
“…In “real” systems, in technology, biology, and oceanography, surfaces are often non-uniform. For instance, a flat surface containing a surfactant monolayer which has undergone a two-dimensional phase separation falls under this definition, as well as air-water and oil-water interfaces with droplets, solid particles, or even thin layers of a microemulsion, foam, or a bicontinuous phase of complex surface thermo and viscoelastic properties (Maestro et al 2015 ; Maestro et al 2014 ; Mazurek and Pogorzelski 2012 ). Addition of surface-active component to seawater can lead to complex formation and affect the interfacial properties (Guzman et al 2014 ).…”
Section: Resultsmentioning
confidence: 99%
“…It could be noticed that protein on water film studies revealed a transition of the film character from a purely elastic ( E i ≪ E d , φ —low, a few degrees) to viscoelastic ( E i ≈ E d , high, φ several dozen degrees), for above the particular value of the strain rate, related to the formation of gelatinous protein molecular complex system (Patino et al 2003 ). Mineral dust particles entrapped in a snowpack are capable of forming surface layers exhibiting significant surface pressures and elasticities similarly like natural sea water surfactants (Mazurek and Pogorzelski 2012 ).…”
Section: Resultsmentioning
confidence: 99%
“…Denotations: π nfilm surface pressure at the breaking point; arrows indicate the temperature scope of the constant β s value therein to the formation of gelatinous protein molecular complex system (Patino et al 2003). Mineral dust particles entrapped in a snowpack are capable of forming surface layers exhibiting significant surface pressures and elasticities similarly like natural sea water surfactants (Mazurek and Pogorzelski 2012). It should be borne in mind that dilatational or compressional deformation of an elastic film-covered water surface will meet opposite resistance force expressed by the corresponding surface tension change:…”
Section: Film Dilatational Viscoelasticity and Surface Tension Gradientsmentioning
confidence: 99%